Polish adaptation of the Highly Sensitive Person Scale - Bobrowska, Magdalena; Liberska, Hanna (Przegląd Psychologiczny, 2023)
Aim: Sensory processing sensitivity is defined as a personality trait that describes the tendency to process stimuli and information more strongly and deeply than others (Aron et al., 2012). The first and most frequently used scale to measure this trait is the Highly Sensitive Person Scale (HSPS) by Aron and Aron (1997). The article presents the process of creating the Polish adaptation of the tool. Method: Exploratory and confirmatory factor analysis were used. The psychometric properties were checked on a sample of 1,360 participants. Results: The obtained results confirm the multifactorial structure of the variable. In the Polish adaptation of the tool (HSPS), two separate factors were recognized: excessive stimulation and depth of processing. Six items were excluded due to their low factor loadings. The results indicate that the Polish version of the HSPS is a reliable tool. Its accuracy is also confirmed by correlations with neuroticism and extraversion, which, according to the theory, are statistically significantly related to the SPS construct (Aron & Aron, 1997). Conclusion: The Polish adaptation of the scale demonstrated good psychometric properties and high reliability. However, research on the cultural aspect of sensory processing sensitivity should be continued, taking into account gender differences.